Research status and development trend of NB-IoT enhancement technology - Furong XU; Weiwen WENG; Chao ZHANG; Tingting BIAN; Xinli MA; Xiangdong GAO; Xin LI; Lei CAO (Dianxin kexue)
NB-IoT,which is the key technology of the Internet of things,has received widespread attention from global operators.Firstly,the commercial technologies of NB-IoT was outlined,then the research status of NB-IoT enhancement technology was introduced in detail from the aspects of mobile IoT enhancement technology,positioning enhancement technology,mobility enhancement technology and intelligent network optimization technology,and finally,future evolution of NB-IoT technology was introduced.